Remote working and teleworking. Some points of reflection in the context of the current SARS-CoV-2 pandemic - Marzena Świstak (Acta Iuris Stetinensis, 2020)
It was the purpose of adopting the Act on particular solutions related to the prevention, countering and combating COVID-19, other infectious diseases and the emergency crises caused thereby of 2 April 2020 to minimise the threat to public life. This was to be attained inter alia by the introduction of the remote work institution. The laconic wording, however, led to various interpretative difficulties as to the scope of obligations of both employers and employees as well as the framework of their mutual responsibility. In order to eliminate ambiguities and ensure the effectiveness of regulations, certain legislative amendments were introduced, but in the current legal circumstances these do not seem to be the target solution. The author, taking advantage of the historic method, was able to show the evolution of the incidental legal solution that is remote work. Based primarily on the dogmatic method, on the other hand, she highlighted the advantages as well as defects of the institution of remote work as it is now, while comparing it to telework. It this context, it was possible to propose certain de lege ferenda (as it should be) conclusions as to the direction of desirable legislative changes, i.e. making the rights and obligations of a remote worker, mutual settlement and rules of responsibility more precise. The main objective of the author was to present possible ambiguities in the current regulations, which should be removed in the legislative works carried out in the future. In this scope, the rules concerning the use and settlement of private equipment, used by the remote worker in the performance of work duties, should be clarified and also the rules concerning the transfer of work results ought to be expressly specified. Further, the author has drawn attention to the unclear limits of responsibility of parties to the employment relationship, where the work is carried out remotely and thus supervision over the worker is lighter. Looking at the global direction of socio-economic changes, it was also suggested that the institution of remote work be regulated in the Polish legal order on the permanent basis.